Adverse reproductive outcomes associated with fetal alcohol exposure: a systematic review. Issue 4 (April 2019) - Akison, L K; Moritz, K M; Reid, N
Abstract : Fetal alcohol exposure results in well-characterised neurobehavioural deficits in offspring, which form the basis for diagnosing fetal alcohol spectrum disorder. However, there is increasing interest in the full range of health complications that can arise in children and adults with this disorder. We used a systematic review approach to locate all clinical and preclinical studies across a broad range of health outcomes in offspring exposed to prenatal alcohol. Our search encompassed four databases (PubMed, CINAHL, EMBASE and Web of Science) and titles/abstracts from retrieved studies were screened against strict inclusion/exclusion criteria. This review specifically evaluated studies reporting on reproductive outcomes in both males and females. A total of 23 studies were included, 5 clinical and 18 preclinical. Although there was a wide range in the quality of reporting across both clinical and preclinical studies, and variable results, trends emerged amongst the reproductive measures that were investigated. In females, most studies focussed on age at first menarche/puberty onset, with evidence for a significant delay in alcohol-exposed offspring. In males, offspring exposed to prenatal alcohol had altered testosterone levels, reduced testes and accessory gland weights and reduced sperm concentration and semen volume. However, further studies are required due to the paucity of clinical studies, the narrow scope of female reproductive outcomes examined and inconsistencies in outcomes across preclinical studies. We recommend that adolescents and individuals of reproductive age diagnosed with f-etal alcohol spectrum disorder be assessed for reproductive dysfunction to allow appropriate management of their reproductive health and fertility.